Shifting Vs Settled Cultivation among Khasi, Garo and Jaintia Tribes of Meghalaya - Ummed Singh, Bankey Bihari, (Indian Journal of Extension Education, 2022)
It is evident from the study that even though the majority of farmers among all three tribes possess low level of knowledge and adoption of improved agricultural technologies, settled cultivation among 37.7% and shifting + settled cultivation among 35.0% of the farmers show that they mayor may not be much aware about improved agril. technologies due to remoteness of the area but with the time they have realized the ill effects of deforestation and the related consequences on the society and the environment and have changed their way of cultivation from shifting to settled.